In the mind of the teacher: Psychoanalytic papers as key elements in a scientific endeavour. (2nd April 2016) - Gonzalez-Torres, Miguel Angel; Fernandez-Rivas, Aranzazu; Penas, Alberto
Abstract: The teaching of psychoanalysis encompasses a wide array of educational stages, from undergraduate students to psychoanalytic candidates and lifelong training for professionals. Papers published in psychoanalytic journals play a fundamental role in teaching tasks. The historical separation of psychoanalytic practice from the research community and the university probably relates to the relative lack of empirical investigation and the contested status of research in general within the psychoanalytic community. In addition, there is not enough debate among different schools and orientations, making it very unlikely that creative solutions to theoretical and practical discussions will be found. Related to this, there seems to be a worrying deficit of recent references in psychoanalytic papers compared with general psychiatric journals or medical publications. This reflects a dangerous attitude of not paying attention to contemporary writers within our own field. Reasons behind this might be fear of confrontation with other colleagues, loyalty to our own dogmas and clinical practices, a system of training that promotes continuity, and even organizational structures that sustain this state of things. A renewed attention to research in psychoanalysis (conceptual, empirical, clinical-observational, etc.) and establishing ties to academic environments in the fields of natural and human sciences might improve this situation and offer a path towards collective theoretical and clinical development.